Application of Discovery Learning Model to Improve Students’ Mathematical Problem Solving Ability on Islamic Junior High School - Ma'ruf, Shofiyah Misbahul; Sari, Indah Puspita; Afrilianto, M. ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
It is important for students to have problem solving abilities, but in the field problem solving abilities are very low. Therefore, the aim of this research is to see an increase in students' mathematical problem solving abilities by implementing the Discovery learning model. This research was conducted at one of the Islamic junior high schools in Bandung Barat regency. This research is experimental research methods. The research sample was class VII B, totaling 18 people. The data collection technique uses tests, namely pretest and posttest with 5 test questions in the form of descriptions to determine students' mathematical problem solving abilities.The data analysis techniques used are prerequisite analysis and hypothesis testing. The results of the research are that the problem solving abilities of students whose learning uses the Discovery Learning model after being given learning are better than before being given the learning. This is shown through the results of the t test using the dependent t test which obtained a significant value (2-tailed) = 0.000. The n-gain test result was 0.5767 or 57.67%, which means that the effectiveness of implementing the Discovery Learning model in mathematics learning is in the medium category or can be interpreted as quite effective. So it can be concluded that the application of the learning model with the Discovery Learning approach can improve student problem solving and help students become more proficient in solving mathematical problem.